Pelatihan Penggunaan Publish or Perish untuk Mahasiswa Pendidikan Matematika Strata 1: Workshop of Publish or Perish Utilization for Undergraduate Mathematics Education Students - Megawanti, Priarti; Andayanti, Westri; Ahmad, Deni Nasir (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The world of writing scientific papers cannot be separated from students' routines. As part of an educated society, the writing process is a means for students to increase their insight, sensitivity, and soft skills before entering the world of work. However, not all students think that writing scientific papers, especially articles, is an easy job. Meanwhile, recently, there have been a lot of software and web applications that can help students compose articles easily, one of which is Publish or Perish. It is hoped that the socialization activity regarding the use of Publish or Perish can increase the enthusiasm and attraction of students to be more active in writing scientific papers. The workshop was carried out in two steps, starting with introducing the software and applying search results to several types of articles, namely bibliometric analysis and systematic literature review. This activity succeeded in motivating participants to write articles and enter them into a competition.